La Translatio sancti Donati (BHL 2295-2296), agiografia aretina del secolo XI - Licciardello, Pierluigi (Analecta Bollandiana, 2008)
The translation of the relics of St Donatus, bishop and martyr, patron of Arezzo, took place in 1023 or 1032 near the suburban basilica of Pionta on the initiative of bishop Teodaldo of Arezzo. The text in which the facts are narrated exists in two redactions (Translatio, BHL 2295-2296) which differ above all towards the end. The present critical edition reconstructs the text of the archetypes of both on the basis of three manuscript witnesses and six editions from the 16th century until the present. In the introductory study the text is analyzed within the context of Tuscan hagiographic works of the 11th century, especially in comparison with the Vita of St Floridus of Città di Castello (BHL 3062).